SELECTION OF LIGHTNING PROTECTION SYSTEM IN OIL & GAS INDUSTRY BASED ON ANALYTICAL HIERARCHY PROCESS - Muliawan Hamzah, Ilham
Since tropical lightning has different characteristics from subtropical lightning, the international standards are not suitable for lightning strikes protection in the oil and gas industry. Various kinds of research have been conducted but none of them comprehensively discussed the protection system in accordance with the standards. In this study, the selection process of a lightning protection system on a floating roof tank is explained based on the Analytic Hierarchical Process (AHP) method. AHP is a tool that can help in choosing the best decision based on certain criteria and conditions. The criterias used in this study are protection area, material requirements, voltage elevation, and voltage induction. The protection systems that are compared are free standing mast with conventional air terminals, free standing masts with early streamer emission air terminals, catenary wire systems, and mesh systems. Based on the analysis, voltage elevation has the most weight amongst other criterias, which is 45,1%. The best protection system according to the AHP method is free standing mast using early streamer emission with a score of 53,94%.